2010
DOI: 10.1111/j.1365-2958.2010.07394.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA topology of highly transcribed operons in Salmonella enterica serovar Typhimurium

Abstract: SummaryBacteria differ from eukaryotes by having the enzyme DNA gyrase, which catalyses the ATP-dependent negative supercoiling of DNA. Negative supercoils are essential for condensing chromosomes into an interwound (plectonemic) and branched structure known as the nucleoid. Topo-1 removes excess supercoiling in an ATP-independent reaction and works with gyrase to establish a topological equilibrium where supercoils move within 10 kb domains bounded by stochastic barriers along the sequence. However, transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 102 publications
6
58
0
Order By: Relevance
“…Similarly, recent experimental work in Caulobacter reveals that highly transcribed genes appear to demarcate topological domains in the chromosome (7), and in vivo measurements of interloci distances in Caulobacter resemble those theoretically predicted for a branched supercoiled conformation with densely packed plectonemes (65). In all three of these organisms, topological domains are measured to possess average sizes of~10 kilobases (7,33) and the importance of transcription in regulating the size of these topological domains is suggested by the high conservation of genomic interspacing of highly expressed genes in the chromosomes of phylogenetically distant bacteria (33). Thus, the linking deficits and length scales simulated in this work are of direct relevance to the length scales and linking deficit regimes that are implicated in transcriptional regulation of chromosomal topology, and may have important implications for chromosomal organization and dynamics.…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 61%
See 3 more Smart Citations
“…Similarly, recent experimental work in Caulobacter reveals that highly transcribed genes appear to demarcate topological domains in the chromosome (7), and in vivo measurements of interloci distances in Caulobacter resemble those theoretically predicted for a branched supercoiled conformation with densely packed plectonemes (65). In all three of these organisms, topological domains are measured to possess average sizes of~10 kilobases (7,33) and the importance of transcription in regulating the size of these topological domains is suggested by the high conservation of genomic interspacing of highly expressed genes in the chromosomes of phylogenetically distant bacteria (33). Thus, the linking deficits and length scales simulated in this work are of direct relevance to the length scales and linking deficit regimes that are implicated in transcriptional regulation of chromosomal topology, and may have important implications for chromosomal organization and dynamics.…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 61%
“…Consistent with this model, both in vitro and in vivo studies indicate that RNA polymerase is a powerful torque generator, and linking deficits below s ¼ À0.10 have been measured as a result of transcription at strong promoters both in the presence of functional Topo I (DNA relaxing enzyme) as well as in Topo I-deficient mutants (28)(29)(30). Studies in E. coli and Salmonella have shown that RNA polymerase is capable of actively creating and remodeling dynamic supercoiled topological domains (6,33). Similarly, recent experimental work in Caulobacter reveals that highly transcribed genes appear to demarcate topological domains in the chromosome (7), and in vivo measurements of interloci distances in Caulobacter resemble those theoretically predicted for a branched supercoiled conformation with densely packed plectonemes (65).…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 65%
See 2 more Smart Citations
“…The writhing of the underwound duplex is described as negative supercoiling (Higgins and Vologodskii 2015). In a bacterium such as Escherichia coli, about half of the DNA supercoils are constrained by interaction with proteins (Bliska and Cozzarelli 1987;Pettijohn and Pfenninger 1980), but the energy in the unconstrained portion is available to drive DNA transactions (Booker et al 2010). The constrained and unconstrained regions of the chromosome are unlikely to be fixed, displaying a dynamism that reflects changes in growth rate, growth phase and changes in the nature and sizes of the populations of DNA binding proteins that decorate the DNA.…”
Section: Introductionmentioning
confidence: 99%